Texturized mung bean protein as a sustainable food source: techno-functionality, anti-nutrient properties, in vivo protein quality and toxicity. Issue 10 (30th September 2020) - Brishti, Fatema Hossain; Chay, Shyan Yea; Muhammad, Kharidah; Rashedi Ismail-Fitry, Mohammad; Zarei, Mohammad; Saari, Nazamid
Abstract : Mung bean is an underutilized yet sustainable protein source. The current work elucidates the pilot-scale production of mung bean protein isolate and reveals good in vivo protein quality which secures TMBP's potential as a protein meal replacement and dietary supplement. Abstract : Mung bean is gaining attention as a sustainable and economic source of plant protein. The current study evaluates the techno-functionality, anti-nutrient properties, in vivo protein quality and toxicity of texturized mung bean protein (TMBP) produced under optimized conditions. Our work successfully produces TMBP with improved techno-functionalities that are crucial for meat-based food applications, credited to retained juiciness and fat-binding ability. Alkaline extraction and extrusion significantly reduce trypsin inhibitor, phytic acid and tannin content in TMBP. An in vivo study using Sprague-Dawley rats reveals the good protein quality of TMBP, with a true protein digestibility of 99.26% resembling casein (99.36%, control protein), a net protein utilization of 63.99% and a biological value of 64.46%. The good protein quality, increased lean muscle mass along with reduced cholesterol and triglyceride secures TMBP's potential as a Protein meal replacer and dietary suplement. Non-toxicity of TMBP is confirmed by normal serum biochemical parameters and healthy organs, ascertaining the safety of alkaline extraction. The current study elucidates the production of TMBP with improved techno-functionalities (for meat-based food applications), reduced anti-nutritional factors and high quality (for weight-watchers and malnourished individuals).